2013
DOI: 10.1177/0959353513510651
|View full text |Cite
|
Sign up to set email alerts
|

Performative shamelessness on young women’s social network sites: Shielding the self and resisting gender melancholia

Abstract: In this paper, I ask what the self-representations of young women on social network sites can tell us about the conditions and experience of inhabiting femininity in the digitally mediated post-feminist context. First, I outline four conditions of post-feminist girlhood that I suggest young women must navigate in the processes of subjectivity construction. I then describe some of the common kinds of performativity found on a small selection of social network site profiles owned by young Australian women. I sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 26 publications
0
47
0
3
Order By: Relevance
“…In a separate analysis (not published here) of the young women's drinking photographs displayed on the SNS Facebook (Atkinson et al, 2015), photographs were found to reflect the notion of the hyper-sexual and feminine 'look', in that short skirts, fake tan and eye lashes, glamorous makeup and the heel in particular, were the basis of their carefully constructed appearance required for participating in nightlife (Bailey et al, 2015;Dobson, 2013;McRobbie, 2009). Photographs commonly depicted and regarded as the 'ideal photo' showed young women posing, in a group, wearing glamorous outfits and makeup, hand on hip, whilst smiling or pouting in a sexual manner, or pulling tongues, whilst holding wine or cocktails (Atkinson et al, 2015;Dobson, 2013).…”
Section: Extractmentioning
confidence: 97%
See 4 more Smart Citations
“…In a separate analysis (not published here) of the young women's drinking photographs displayed on the SNS Facebook (Atkinson et al, 2015), photographs were found to reflect the notion of the hyper-sexual and feminine 'look', in that short skirts, fake tan and eye lashes, glamorous makeup and the heel in particular, were the basis of their carefully constructed appearance required for participating in nightlife (Bailey et al, 2015;Dobson, 2013;McRobbie, 2009). Photographs commonly depicted and regarded as the 'ideal photo' showed young women posing, in a group, wearing glamorous outfits and makeup, hand on hip, whilst smiling or pouting in a sexual manner, or pulling tongues, whilst holding wine or cocktails (Atkinson et al, 2015;Dobson, 2013).…”
Section: Extractmentioning
confidence: 97%
“…Among this group of young women, SNS were discussed in ways that reinforced drinking as important to the friendship group by acting as an extension of the space in which they documented the fun and pleasurable interactions bound up with their active social lives as post-feminist subjects through uploading drinking photographs to SNS (Dobson, 2013;Goodwin et al, 2016;Hutton et al, 2016). Moreover, they provided the opportunity for being seen, for expressing popularity and for peer attention and appraisal through practices such as Facebook likes and comments .…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations